Problem 7-19 Determination of Lime and Soda Ash Dose for Water Softening - Stone, James (McGraw-Hill's AccessEngineering., 2017)
This video shows how to calculate the amount of lime and soda ash required for water softening based on given source water constituents and treatment requirements.